The transcendental object and the “problem of affection”. Remarks on some difficulties of Kant’s theory of empirical cognition (Diametros, 2013)
The paper presents one of the sources of the incoherence objection to Kant’s transcendental idealism, i.e. the problem of “affection” between the “transcendental ground” and mental representations. It is divided into two sections: in the first the historical context of the problem is sketched; in the second two contemporary solutions to the problem are suggested. The latter include N. Rescher’s “conceptual idealist” interpretation, which postulates a logical (rational) relation between representational content and its “ground”, and A. Brook’s cognitivist explanation, which appeals to a materialist hypothesis that makes use of a kind of correlation between the mental and the physical. The conclusion grants both stances considerable plausibility, admitting that, as often is the case, Kant’s way of posing questions here too leads to contradictory answers. It seems that the options suggested cannot be reconciled: one has to choose between the presence of metaphysics in Kant’s critical philosophy or the naturalization of transcendental philosophy. This state of affairs reflects the history of Kant’s interpretations.